Green sustainable process for chemical and environmental engineering and science. - Inamuddin, 1980-; Altalhi, Tariq (Elsevier, 2023)
Green Sustainable Process for Chemical and Environmental Engineering and Science: Carbon Dioxide Capture and Utilization explores advanced technologies based on CO2 utilization. The book provides an overview on the conversion and utilization of CO2, extraction techniques, heterogeneous catalysis, green solvent, industrial approaches, and commodity products through energy-intensive processes. In addition, it highlights lifecycle assessment and biological and engineering strategies for CO2 utilization. Each chapter presents challenges in the processes and future perspectives for the application of CO2 conversion and utilization.